A Five-Year Analysis of Mortality Causes in Western Iran (2015-2019) - Hasan Ebrahimpour Sadagheyani; Hamid Bouraghi; Ali Mohammadpour; Pegah Khazaei; Farzaneh Kimiaei; Marzieh Naderishahab (Shiraz University of Medical Sciences, 2024)
Background: Mortality statistics serve as a crucial component in community health planning systems. The causes of death can vary across different geographical areas due to factors such as indigenous culture and lifestyle. This study aimed to investigate the mortality trends and their causes from 2015 to 2019 in Hamedan province, located in the west of Iran.Methods: This cross-sectional study examined all deaths (43,515 individuals) in Hamedan province from 2015 to 2019. Death data, including demographics and the underlying cause of death, were extracted from the mortality system of the Hamedan Health Center. Data collection utilized a checklist corresponding to the International Death Certificate issued by the WHO. Data analysis was performed using SPSS ver. 26.Results: In 2019, the average monthly death rate was the highest compared to previous years (766.3±39.1), while this number for 2015 was 682.2±37.7. In 2019, U codes (for Emerging diseases) were used for Covid-19. The mean age of deceased females (73.3±18.2) was higher than that of deceased males (67.0±20.6), showing a significant difference (P<0.001). The top three causes of death in Hamedan during these years were cardiovascular diseases (CSDR=46.7%), neoplasms (CSDR=13.8%), and external causes of injuries (CSDR=8.8%), respectively.Conclusion: The analysis of the findings indicates that health plans aimed at preventing mortality factors have not been very effective. Therefore, it is recommended that health officials in Hamedan province monitor mortality data and devise effective plans to control mortality factors. As these preventive plans cannot be implemented solely by the Hamadan University of Medical Sciences, other organizations in the province involved in public health need to play an effective role.